عصرحاضرکے معاشرتی مسائل کاحل:مولانا محمداکرم اعوان کے افکار کی روشنی میں ایک مطالعہSolutions to Contemporary Social Problems: A Study in the Light of Mawlānā Muhammad Akram Āwan’s Thoughts (Al-Qamar, 2021)
The present age is again reflecting the conditions of the sixth century AD. The Prophet of Islam, peace and blessings be upon him, created a historic and unprecedented revolution. And human history is a witness that the best time of all times is when the Muslim Ummah follows its great Prophet, the Prophet of Mercy and spending days and nights in it. As time passed by, the Muslim Ummah began to suffer from negligence in following its beloved Prophet (peace be upon him), due to which every coming time began to present a severe situation. The most important social problems that are being faced today are corruption, lack of trust in Allah. Lack of Trust and turning away from following the Prophet (PBUH), usury, proselytizing, intellectual, practical, and moral decline and terrorism, deterioration of family system, bad culture, bad peace and bad order, restlessness and mental pressure, materialism etc. are important. In every era, the thinkers had the pain of the Ummah, made efforts to reform it. Sheikh e Silsila Naqshbandiyya Owaisiya and Ameer Tanzeem Al-Ikhwan, Maulana Muhammad Akram Awan (R.A), is one of the great thinkers of the nineteenth and twentieth centuries who offered their services in every field of life. In this Article, solution of such Problems in the light of the thoughts of Maulana Muhammad Akram Awan are discussed.